Kode Lakuan Perempuan dalam Naskah Qurtubi Karya TGH. Alimuddin Praya Nusa Tenggara Barat - Lalu Kamarudin; Syahdan Syahdan; Johan Mahyudi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study examines codes of conduct of women in carrying out their life according to the Qurtubi text by TGH. Alimuddin Praya West Nusa Tenggara. As the Islamic text from which values of women conducts based on hadits and the exemplars of Siti Fatimah, the daughter of the Muhammad Prophet, the text has been referenced as the core value of teaching for the society. This study used content analysis where themes and constructs of morale were focused from the text. The study used is a qualitative approach with descriptive analytical method, namely a method that expresses the actual situation in the text. Data were collected using documentation techniques, interviews and content analysis. The results show the code of conduct of women is conveyed through dialogue and actions experienced by the character depicted in the TGH Qurtubi text of Alimuddin Praya Lombok West Nusa Tenggara. The description of the action includes three codes, namely: 1) codes of conduct of women that depict social goodness, 2) codes of conduct of women that describe acts of conflict, and 3) codes of conduct of women that describe the attitude of guard and maintain. This teaching implies that codes of conduct of the women indicate the attitude to develop understanding, actions or the nature of maintaining positive norms that are not contrary to the values ​​of religion, culture or customs that apply.